TIMING OF GLYCEROL ADDITION ON SPERM QUALITY IN CRYOPRESERVATION OF CANINE SEMEN - Carlotto R., Gino (2011)
The objective of the study was to evaluate the timing of adding glycerol during thecooling process on sperm quality of canine semen. Fifteen ejaculates from 4 mature dogswere used. Each sample was divided in aliquots and three methods of adding glycerolwere used (T1: at the beginning; T2; at the beginning and at the end; T3: at the end of thecooling process). Semen samples were packed in 0.5 ml straws and frozen in liquid nitrogen.The post-thawing progressive motility and the functional integrity of membrane wereevaluated. None statistical difference was observed due to the three treatments, indicatingthat the process of cryopreservation can be simplified by adding all the glycerol at thebeginning of the cooling curve.